Estimation of Impact of Quantitative Easing Policy on EUR/USD using behavioral Equilibrium Exchange Rate Model - A. A. Vinogradov (Финансы: теория и практика, 2019)
The article examines the impact of the policy of the uSA quantitative easing and the euro area on the nominal EuR/ uSD exchange rate. After the economic crisis of 2008–2009, the policy of quantitative easing gained popularity among the world’s largest economies. The largest programs were implemented by the uS Federal Reserve (uS Federal Reserve System) and the European Central Bank (ECB). However, the impact of the actual purchase volume of securities on the EuR/uSD exchange rate within these policies has been little studied in modern literature. The author collected the data from 1999 to 2018 on the exchange rate, macroeconomic and market indicators, and calculated the monthly actual purchase volumes of securities under the asset purchase program of the united States and the euro area. The behavioral equilibrium exchange rate model was used. The linear model specification and the error correction model identified no significant impact of the ECB quantitative easing policy expressed in the actual purchase volume of securities. However, for some specifications, it has been proven that the increase in purchases of securities by the uS Federal Reserve leads to a weakening of the dollar against the euro. The cointegration test revealed a long-term dependence of the EuR/uSD exchange rate on the accumulated volumes of acquired assets. Thus, an increase in the purchase volume of securities led to a weakening of the dollar against the euro. The insignificant impact of the European Central Bank quantitative easing policy could have been caused by market expectations formed prior to the actual purchase of ECB securities in the market.